المشكلات الفقهية من خلال الشرح الكبير للدردير ت(1201ه ) دراسة تأصلية تطبيقية -نماذج مختارة - باهي, عبير (University of Eloued-جامعة الوادي, 2022)
" تُعدّ هذه الدراسة المـَوْسُومَةُ بـــ"" المشكلات الفقهية من خلال الشرح الكبير للشيخ الدردير""، دراسة تأصيلية تطبيقيّة للمشكلات الفقهية، وهو إجابة عن اشكالية مفادها؛ "" ما المشكلات الفقهية التي أَوْرَدَها الدردير في الشرح الكبير وما منهجه في دراستها؟"". وقد عالجتُ هذا الإشكال بالاعتماد على خطّة، تتكون من مقدمة، ومبحثين، وخاتمة. فكان المبحث الأول عبارة عن دراسة نظرية للمشكلات؛ أَوْرَدتُّ فيه تعريفًا للمشكلات الفقهية، كما بيَّنْتُ وجه العلاقة التي تربط المشكلات الفقهيّة بما شاكلها من مصطلحات، وذكرت لمحة تاريخية عن التأليف فيها. كما تحدّثْتُ عن أقسام المشكلات الفقهية وأهميتها، ثمّ أوردت ترجمة للمُؤَلِّف والمـُؤَلَّف، سبقها بيان لمنهج الدردير في دراسة المشكلات الفقهية. أمّا المبحث الثّاني فكان دراسة تطبيقية للمسائل المـُشكلة التي وردت في الشرح الكبير؛ اخترتُ فيه مسائل، من قسم العبادات( باب الطهارة والصلاة)، وقسم المعاملات( باب النكاح والبيوع)، كانت هذه المسائل عبارة عن نماذج مختارة؛ بلغت أربعة عشرة مسألة مُشكلة. وأخيرًا خَتَمْتُ المذكرة؛ ببيانٍ لأهم النتائج المـُتوصّل إليها من خلال البحث، متبوعة بفهارس فنية تكشف محتوى البحث. "This study, labelled ""Jurisprudence Problems through the Great Explanation of ElDadir Sheikh"", is an applied investigative study of jurisprudence problematique, an answer to a problematic one: """"What jurisprudence problems did ElDadir mention in the big explanation and what did he approach in her study?"" I have addressed these forms by drawing on a plan, consisting of an introduction, researchers, and a conclusion. The first was a theoretical study of problems; I set out a definition of jurisprudence problems, and also outlined the relationship that connects jurisprudence problems with the terminology that they constitute, and a historical overview of the composition therein. I also talked about the sections of the jurisprudence and their importance, and then gave a translation of the author and author, preceded by a statement of ElDadir approach to the study of the doctrinal problems. The second examination was an applied study of the problem issues identified in the large commentary; In which I chose matters, from the Department of Worship (Door of Purity and Prayer), and the Department of Transactions (Door of wedding and Sales), these issues were selected models; Fourteen issues are problematic. Finally, I concluded the memo; An account of the most important findings obtained through research, followed by technical indexes that reveal the content of the research. "
مذكرة ماستر
Keywords: مشكل - دردير - مسائل المشكلة; Problem - Dardir - Problem issues